Organizational effectiveness (Vikas, 2013)
Organizational effectiveness is the concept of how effective an organization is in achieving the outcomes it indents to produce. he success or failure of organizations is, to a great extent determined by employees. Employees exhibit many forms of behavior, which have a significant impact on the performance and growth of organizations, followed by features and role of organizational behavior. The book also explains the importance of conflict management and organizational change and development